The Balloon-borne Large-Aperture Submillimeter Telescope for polarization: BLAST-pol - art. no. 702002 - Marsden, G; Ade, PAR; Benton, S; Bock, JJ; Chapin, EL; Chung, J; Devlin, MJ; Dicker, S; Fissel, L; Griffin, M; Gundersen, JO; Halpern, M; et al. (SPIE-INT SOC OPTICAL ENGINEERING, 2008)
The Balloon-borne Large Aperture Submillimeter Telescope (BLAST) is a, sub-orbital experiment designed to study the process of star formation in local galaxies (including the Milky Way) and in galaxies at; cosmological distances. Using a 2m Cassegrain telescope, BLAST images the sky onto a focal plane, which consists of 270 bolometric detectors split; between three arrays, observing simultaneously in 30% wide bands, centered at 250, 350, and 500 mu m. The diffraction-limited optical system provides a resolution of 30" at 250 mu m. The pointing system enables raster-like scans with a positional accuracy of similar to 30", reconstructed to better than 5" rms in post-flight analysis. BLAST had two successful flights, from the Arctic in 2005, and from Antarctica in 2006, which provided the first high-resolution and large-area (similar to 0.8-200 deg(2)) submillimeter surveys at these wavelengths. As a pathfinder for the SPIRE instrument on Herschel, BLAST shares with the ESA satellite similar focal plane technology and scientific motivation. A third flight in 2009 will see the instrument modified to be polarization-sensitive (BLAST-pol). With its unprecedented mapping speed and resolution, BLAST-pol will provide insights into Galactic star-forming nurseries, and give the necessary link between the larger, coarse resolution surveys and the narrow, resolved observations of star-forming structures from space and ground based instruments being commissioned in the next 5 years.